Li2xMg(1-x)O light absorption properties for semiconductor applications / Nor Fadilah Chayed … [et al.] - Chayed, Nor Fadilah; Kamarulzaman, Che Norlida; Batar @ Badar, Nurhanna; Rusdi, Roshidah; Elong, Kelimah (Research Innovation Business Unit, 2014)
Substitution of cation in metal oxides could give different properties with potential in some application such as semiconductor. Li2xMg(1-x)O was prepared by substitution of magnesium with lithium in magnesium oxide to form new materials Li2xMg(1-x)O (x= 0.1, 0.2) which were Li0.2Mg0.9O and Li0.4Mg0.8O. Both MgO and Li2xMg(1-x) O were synthesized by using a sol-gel method. The sample were named M1 (MgO), M2 (Li0.2Mg0.9O) and M3 (Li0.4Mg0.8O). The samples were characterized by using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The band gap energies of the samples were obtained from measurements using a UV-Vis Spectrophotometer. The XRD patterns of lithium substituted samples are isostructural with the ICDD pattern of MgO (ICDD No. 01-074-1225). No impurity peaks could be observed. The peak positions are slightly shifted to the right as is illustrated by the shift of the (200) reflection and this is true with the other peaks as well. This implies that the cell parameters have decreased and it can only happen if the smaller ionic radius Li+ ions have been successfully substituted into the crystal lattice of the MgO. The ionic radii of the ions, Li+ and Mg2+, are 0.76 angstrom and 0.72 angstrom respectively according to coordination number 6 (cubic structure). Therefore, lithium can be said to have been successfully introduced into the crystal lattice of the material and the substitution reaction is deemed successful. It is observed that the average crystallite size of M2 and M3 samples are much bigger than although the annealing time and temperature is the same. This shows that the thermal characteristics of the Li2xMg(1-x)O are quite different from the pure MgO. The rate of crystal growth of the materials with more lithium content is higher as can been seen with the large crystallite size of highest lithium content sample (M3). Thus, the amount of lithium content in the samples seems to affect the rate of crystal growth. It was found that there were quite drastic differences in the band energies of MgO and Li2xMg(1-x)O materials. The band gap energy for MgO is 5.13 eV which is lower than conventional value (7.8eV) by about 34%. There are two absorption edges for the Li containing samples instead of just one as observed for the MgO sample. The edges have a gradual slope and this is very different from that of the absorption edge of MgO which has a distinctly sharp edge. The positions of the absorption edges are towards the lower wavelength region and correspond to band energies of 2.82 eV and 2.90 eV for first absorption edge and 1.83 eV and 1.98 eV for second absorption edge. These very different spectra observed for the Li substituted samples is another proof of the formation of new Li0.2Mg0.9O and Li0.4Mg0.8O compounds. Materials are uniquely characterized by their band gaps. It is observed that the larger the Li content the larger the band energies. The observed red shift may be because the presence of Li may have caused hybridization and introduced more energy levels in-between the MgO gap. The substituted materials, Li2xMg(1-x)O have band gaps of between 1.83 eV to 2.90 eV which make it usable as semiconductor materials.